PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEBSITE (STUDY KASUS DI TK AL MUJAHIDIN) - Muhtajuddin Danny; Khoiriyah Khoiriyah (Jurnal SIGMA, 2019)
Research on the acceptance of new students at TK Al Mujahidin is still conventional. TK Al Mujahidin itself is an educational park located in the Cikarang area. With the influence of current technological advances, the authors create a new system to develop the old system of admitting new students at TK Al Mujahidin, which aims to become an information medium in introducing schools to the world of technology education as well as a forum for new management of student data in schools. Developing the old system into a website-based information system, where in this study using waterfall modeling and making a system design described by the Unified Modeling Language (UML). The result of this research is that the admission of new students at TK Al Mujahidin is already website-based, and can be used to facilitate the dissemination of new student registration information in filling out forms and requirements to become students at TK Al Mujahidin. In this case, the new student admission information system can facilitate the delivery of information in the form of registration, biodata, lesson schedules and uploading documents that are useful for reducing the accumulation of existing data. This website is built using the MySQL database as well as the programming language PHP and HTML and BOOTSTRAP in displaying the user interface. Keywords: Online Registration, Information Media, Education, Waterfall, UML, MySQL, PHP, HTML, BOOTSTRAP.